2001
DOI: 10.3727/000000001783986639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Extracellular Matrix on Pancreatic Endocrine Cell Function and its Biocompatibility in Dogs

Abstract: The effect of the synthetic extracellular matrix (ECM) in a diffusion chamber for a bioartificial endocrine pancreas (Bio-AEP) on pancreatic endocrine cells in vitro and its biocompatibility in dogs were investigated. Two different types of ECM were used: type I collagen treated with low antigen (type I LA), and reconstituted basement membrane matrix (Matrigel) derived from Englbreth-Holm-Swarm (EHS) mouse sarcoma. Matrigel contains growth and differentiation factors and cell adhesion molecules such as laminin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…The evidence presented here, showing an increased insulin accumulation in the presence of Matrigel, is in good agreement with previous data showing the effect of this product on the maintenance of normal cell function (Perfetti et al 1996, Edamura et al 2001, Oberg-Welsh 2001. However, in contrast with the transdifferentiation/ differentiation effect that has been described for islet (Kerr-Conte et al 1996), acinar (Arias & Bendayan 1993) and ductal cells (Bonner-Weir et al 2000), our attempt to promote differentiation of nestin-positive cells by subculturing onto a Matrigel-coated surface only induced cell migration and formation of islet-like clusters after 24 h, with unaltered insulin and nestin expression levels.…”
Section: Days In Culturesupporting
confidence: 92%
“…The evidence presented here, showing an increased insulin accumulation in the presence of Matrigel, is in good agreement with previous data showing the effect of this product on the maintenance of normal cell function (Perfetti et al 1996, Edamura et al 2001, Oberg-Welsh 2001. However, in contrast with the transdifferentiation/ differentiation effect that has been described for islet (Kerr-Conte et al 1996), acinar (Arias & Bendayan 1993) and ductal cells (Bonner-Weir et al 2000), our attempt to promote differentiation of nestin-positive cells by subculturing onto a Matrigel-coated surface only induced cell migration and formation of islet-like clusters after 24 h, with unaltered insulin and nestin expression levels.…”
Section: Days In Culturesupporting
confidence: 92%
“…These findings might be associated with some type of immune response to the Bio-AEP. In our previous investigation on the biocompatibility of the Bio-AEP without PE-cells in normal dogs, immunological reactions to the silicon ring, nuclepore membrane, and the ECM with type-I collagen treated to reduce the antigenicity were not detected for at least 3 months after implantation [4,5]. The present findings suggested that PE-cells might induce some type of immune response in the recipient, leading to fibrous tissue encapsulation.…”
Section: Discussioncontrasting
confidence: 40%
“…For example, fibronectin has been shown to inhibit apoptosis 23 and laminin, to increase long term culture preservation. 24 The importance of cell matrix interactions for optimal regulated insulin secretion is supported by several studies on β-cells cultured on various crude matrices or their purified extracts. [25][26][27] Besides, β-cells cultured on 804G matrix have been shown to increase the basal and stimulated insulin release.…”
Section: Resultsmentioning
confidence: 99%